2020
DOI: 10.1371/journal.pone.0232554
|View full text |Cite
|
Sign up to set email alerts
|

Evapotranspiration and crop coefficients of Italian zucchini cultivated with recycled paper as mulch

Abstract: Recycled paper has the potential to be used as a mulch for vegetable production and can be adopted for the cultivation of Italian zucchini. However, there have been no studies about the water savings or crop coefficient values used in irrigation management in this system; therefore, there is a need for more research. In view of the above, this study aimed to evaluate the effects of recycled paper mulch on evaporation and evapotranspiration in Italian zucchini and to determine the crop coefficients in its devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 34 publications
1
4
0
Order By: Relevance
“…It is verified that the R 2 values found in this study are lower than those found for different crops (Alface et al, 2019;Mahmoud and Gan, 2019;Oliveira et al, 2020). In these studies, some crops, such as sugar cane, wheat, potato, sorghum, zucchini, etc., were evaluated and, in all of them, R 2 was above 70%.…”
Section: Estimation Of Et W /Eto Ratio By Ndvisupporting
confidence: 72%
“…It is verified that the R 2 values found in this study are lower than those found for different crops (Alface et al, 2019;Mahmoud and Gan, 2019;Oliveira et al, 2020). In these studies, some crops, such as sugar cane, wheat, potato, sorghum, zucchini, etc., were evaluated and, in all of them, R 2 was above 70%.…”
Section: Estimation Of Et W /Eto Ratio By Ndvisupporting
confidence: 72%
“…They subtracted it from the known distributed water from dams to estimate the groundwater demand in an integrated modeling of demand and supply of water. This method exploited previous works on the determination of crop coefficients [51][52][53][54][55][56][57][58][59] to estimate actual evapotranspiration [60] by relying upon remote sensing-based vegetation indices [61][62][63][64]. The crop coefficient was also used as a supplement in a parameterized water balance approach by Saadi et al [65] in order to show growth conditions.…”
Section: Quantification Methodsmentioning
confidence: 99%
“…VIs have proven to be more effective than leaf growth and physiological characteristics in selecting superior treatments (Table 5 and Figure 6). Oliveira et al [66] reported decreased water consumption in Italian zucchini (Cucurbita pepo L.) when mulched with recycled paper. They demonstrated the utility of VIs by showing a positive/strong R 2 = 0.73 relationship between the crop coefficient and the NDVI.…”
Section: Discussionmentioning
confidence: 99%